The mythographic Chaucer : the fabulation of sexual politics - Chance, Jane, 1945- (University of Minnesota Press, 1994)
Jane Chance reveals how the concealment of embarrassing secrets often sexual in nature and the burden of political alliances and strategies-what might together be termed sexual politics-motivated Chaucer in much of his work. Firmly placing Chaucer in the cultural politics of his time, she shows how he manipulated the mythographic and textual conventions of the period for his own literary, social, and political purposes.